2013
DOI: 10.4025/actascitechnol.v35i2.13364
|View full text |Cite
|
Sign up to set email alerts
|

Zinc adsorption in bentonite clay: influence of pH and initial concentration

Abstract: ABSTRACT. This paper evaluated the adsorption capacity of zinc by Bofe bentonite clay. Bofe clay was subjected to a thermal treatment for optimizing its adsorption capacity. The kinetic equilibrium of the process was studied in a finite bath system and experiments were performed by varying pH, the amount of adsorbent and initial concentration of the metal. The Langmuir and Freundlich models were used for the analysis of adsorption equilibrium. The physicochemical characterization of clay, before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The chemical analysis presented in Table 2 shows that the bentonite clays consist mainly of silica and alumina with metallic oxides such as Fe2O3, K2O, CaO, etc., present as minor. The most abundant components are Si and Al, which are the smectite clay group [5]. Generally, the Al2O3/SiO2 ratio obtained is 0.34 and 0.30 for natural and HDTMA-Br modified Dijah-Monkin clays, respectively, which is in close agreement with the expected value (i. e. 0.33) for montmorillonite [1].…”
Section: Resultssupporting
confidence: 85%
“…The chemical analysis presented in Table 2 shows that the bentonite clays consist mainly of silica and alumina with metallic oxides such as Fe2O3, K2O, CaO, etc., present as minor. The most abundant components are Si and Al, which are the smectite clay group [5]. Generally, the Al2O3/SiO2 ratio obtained is 0.34 and 0.30 for natural and HDTMA-Br modified Dijah-Monkin clays, respectively, which is in close agreement with the expected value (i. e. 0.33) for montmorillonite [1].…”
Section: Resultssupporting
confidence: 85%
“…The elemental composition shows the presence of K and Ag in minor quantity while Ti and Mn are in trace amounts. The most abundant component of Si and Al in the sample confirmed the basic elements of the smectite clay group (Araujo et al 2013). The high iron content explained the brownish and reddish appearance of bentonite clay.…”
Section: Characteristics Of Bentonite Adsorbentmentioning
confidence: 64%
“…This fact suggests that both bentonites can be applied in the sorption of metal ions as Ag + . Araujo et al studying a natural bentonite from Paraiba for Zn 2+ sorption found a PCZ of 6.0, while Kim found 8.0. However, a lower value for PCZ was found by Mekhamer studying a Saudi bentonite (PZC = 3.0).…”
Section: Resultsmentioning
confidence: 99%